PROBLEMS OF THE PROFIT TAX FOR COMPANIES WHICH TAKE THE IMPORT PROCEDURE - V. Senkov; N. Shchukin (Вестник университета)
The article affects problems of the profit tax for companies. There was considered arbitration experience about importing of fixed assets to the Russian Federation.